Related party transactions and corporate tax management: insights from a systematic literature review - Ramadanty, Jesica; Sihombing, Belandina Anita Sere; Fuadah, Luk Luk (Nur Science Institute, 2025)
This study aims to systematically analyse the existing literature on Related Party Transactions (RPT) and their implications for corporate tax management. Using a systematic literature review method, 28 peer-reviewed articles published between 2019 and 2024 from Scopus-indexed journals were selected based on predefined inclusion criteria. The review reveals that RPT is closely associated with various corporate outcomes such as earnings management, tax avoidance, firm value, and financial reporting quality. The findings indicate that while some studies support the opportunistic view of RPT and linking it with aggressive tax strategies, others present a more efficient perspective, highlighting RPT as a means of resource allocation and internal financing. The research identifies Agency Theory as the most dominant theoretical lens, followed by Stakeholder Theory, Resource Dependence Theory, and others. Independent variables examined in the literature include RPT types, board characteristics, ownership structure, CSR/ESG disclosure, and institutional factors, while dependent variables range from earnings management to tax avoidance and firm value. The analysis also highlights inconsistencies in empirical results, driven by differences in institutional contexts, regulatory environments, and moderating variables such as CSR, board independence, and audit quality.